Paleomagnetic evidence for multiple late Cenozoic glaciations in the Tintina Trench, west-central Yukon, CanadaThis article is a companion paper to Duk-Rodkin et al., also in this issue. - Barendregt, René W.; Enkin, Randolph J.; Duk-Rodkin, Alejandra; Baker, Judith (Canadian Journal of Earth Sciences, 2010)
The Tintina Trench in west-central Yukon has preserved an extensive record of late Cenozoic preglacial, glacial, and interglacial deposits. These deposits comprise multiple sequences of tills, outwash, loesses, and paleosols. The sediments that were laid down directly by ice (tills) are of both local (montane) and regional (Cordilleran) provenance. The Tintina Trench area was impacted repeatedly by montane ice from the southern Ogilvie Mountains to the northwest (2500 m above sea level (asl)), and also repeatedly along its southern extent by Cordilleran ice from the Selwyn Mountains to the east (2759 m asl), the latter forming the continental divide in this region. We report here the magnetostratigraphy of three sections: Rock Creek (64°13′N, 139°07′W), West Fifteenmile River (64°29′N, 139°55′W), and East Fifteenmile River (64°23′N, 139°48′W). The majority of the units identified at these sections record late Pliocene to mid-Pleistocene glaciations, although relatively thin surficial sequences of late middle Pleistocene to late Pleistocene loesses and tills are present as well. Of the 11 units described in the Tintina Trench, seven have normal polarity, three have reversed polarity, and one has an undefined polarity. These units span about 3.0 million years. It appears that most of the polarity chrons and subchrons of the late Cenozoic are present and that the sequence of six reversals record at least 10 glaciations (three in the Brunhes Chron and seven in the Matuyama Chron), and 11 interglaciations (four in the Brunhes Chron and seven in the Matuyama Chron). The interglacials are recorded as either paleosols or unconformities between glacial or loess units having opposite polarity. While not all Matuyama Chron glacial and interglacial cycles recorded in marine isotopic records are seen on land, the terrestrial records found in the Tintina Trench have thus far proven to be the most complete in terms of the polarity record. While no absolute ages were obtained from the sediments in the trench, the extensive ...